Entomopatogen nematode exploration and virulency against Spodoptera frugiperda J.E Smith - Winda Septi Hade; Djamilah Djamilah; Priyatiningsih Priyatiningsih (Badan Penerbitan Fakultas Pertanian (BPFP), 2020)
Corn (Zea mays L) is a very important food and animal feed after rice. One of the important pests that attack corn plants is Spodoptera frugiperda J.E Smith. This pest is a new pest and is a major pest in corn. In pest control, farmers generally use synthetic chemicals. In an effort to reduce these negative impacts synthetic chemical, entomopathogenic nematode (NEP) was chosen as one of the more environmentally friendly control techniques. This study aims to obtain NEP isolates, population density and virulence against S. frugiperda. This research was conducted at the Plant Protection Laboratory, Bengkulu University from December 2019 to April 2020. This study used a Factorial Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments consisted of NEP concentrations : 0 Jl / ml; 200 Jl / 1ml; 400 Jl / 2ml; 600 Jl / 3ml originating from Bengkulu and Kepahiang isolates. Each experiment consisted of 3 S. frugiperda larvae. The results showed that the NEP obtained from each region, namely the genus Steinermatidae. Population density of 9,005 NEP / 5ml in the Kepahiang area and 6,837 NEP / 5ml in the Bengkulu region. NEP virulence test against S. frugiperda larvae showed that 200 Jl / ml concentration was able to control S. frugiperda in maize , and can kill pests within 4 days. With an LC50 value of 163.5 Jl / ml in Kepahiang isolates and 186.5 Jl / ml in Bengkulu isolates.